Novel Homozygous TTI2 Variant Causing Autosomal Recessive Syndromic Intellectual Disability and Primary Microcephaly from Pakistan: A Case Report (Exome Report) - Zul Qarnain; Fatima Khan; Fizza Akbar; Salman Kirmani (Case Reports in Genetics)
We describe a male patient with a novel TTI2 variant, which has not been previously associated with a human phenotype. His features include intellectual disability, primary microcephaly, delayed psychomotor development, speech delay, short stature, dysmorphic facial features, esotropia, kyphoscoliosis, and behavior abnormalities (Figure). Next generation sequencing revealed autosomal recessive TTI2 variant with uncertain significance, denoted as c.21_22insAAGCGCTCTG (p.Glu8Lysfs × 12). TTI2 encodes a regulator of DNA damage response and helps maintain steady levels of the PIKK family of protein kinases. No disease-causing variants in other genes potentially linked to his clinical presentation were identified. We report a novel loss-of-function homozygous variant in TTI2 that leads to syndromic intellectual disability and primary microcephaly.